Problematika Kompetensi Verbal Guru Bahasa Indonesia di Kelas - Lutfitasari, Wevi; Dwi Sudarto, Yoharwan (Yayasan Arrahman Nahdlatul Wathan, 2023)
This study aims to review the problems of teacher pedagogical competencies, especially communication competencies that must be developed by teachers to interact with students. These problems were obtained through a critical review of research articles related to teacher communication competence in learning. There are three problems faced by teachers related to the implementation of their communication competence, namely problems in giving praise, receiving ideas, and motivating students. These problems can be minimized by developing transformative humanistic and intellectual education.